Development of an elevator simulator to support problem-based electric motor control practicum for vocational high school student - Dadan Nurdin Bagenda; Noor Cholis Basjaruddin; Endang Darwati; Edi Rakhman (invotek, 2021)
Workers who can control electric motors are currently needed. Therefore, knowledge about controlling electric motors should be taught in vocational high schools. Installation and control of electric motors in the industry are generally used in various devices related to the production process such as controlling the motor driving conveyor belts, controlling pumps on factory pipes, and controlling freight elevators. The problem that arises is the lack of knowledge about electric motor control in vocational school teachers and insufficient facilities for the learning process of electric motor control. Also, Vocational High School (SMK) has not been able to change the old learning patterns to the new learning patterns required in the 2013 curriculum. One of the changes in the curriculum is a change from teacher-centered learning to student-centered learning. In this service program, learning the installation and control of electric motors in the simulator of elevators was developed using the Problem Based Learning (PBL) approach for students of SMKN 1 Cipatat. The first step in implementing this program is to study the curriculum and syllabus applied to the two partner vocational schools, then design a learning process for the installation and control of electric motors using the PBL method. The PBL method was chosen because this method can simultaneously be used to increase students' soft skills such as the ability to innovate, discipline, and the ability to convey ideas both in writing and orally. Besides, the PBL method can also support changes to learning patterns as required in the 2013 curriculum.